Static characteristic analysis of a transmission line detection robot. Issue 1 (January 2020) - Wen, Guang; Su, Rui; Yao, Kun; Zuo, Fangjun; Wu, Xuefeng; Hui, Chongli
Abstract: The functions of the transmission line inspection robot mainly depend on the metal structure. Whether the strength of the metal structure meets the requirements is directly related to the reliability of the robot. Taking a flying-wheel transmission line inspection robot as the research object, the static characteristics of its metal structure under common load conditions are analyzed by finite element software, and whether the strength of the structure meets the application requirements is investigated. Through analysis, it is found that the maximum working stress of the metal structure of the robot under working load appears near the left wheel pressure, and its value is less than the allowable stress of the material. With the increase of wind pressure, the maximum working stress of the mechanical structure of the robot increases.